2021
DOI: 10.1002/14651858.cd005084.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for tobacco cessation delivered by dental professionals

Abstract: Analysis 4.1. Comparison 4: Behavioural support from dental professional at high school/college versus usual care/no intervention, Outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 107 publications
0
27
0
3
Order By: Relevance
“…Several studies have tested the delivery of brief behavioral interventions focused on tobacco cessation and found them to be effective [ 32 , 33 , 34 , 35 ]. A recent international Cochrane review of trials in dentistry (including 13 U.S. studies) found overall positive (but low-certainty) evidence that brief intervention from dental providers alone increases quit rates, although the level of evidence was more robust (moderate-certainty) when such brief intervention was paired with access to pharmacotherapy [ 36 ]. Research on SBIRT for alcohol and other substance use in dentistry is far more limited.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have tested the delivery of brief behavioral interventions focused on tobacco cessation and found them to be effective [ 32 , 33 , 34 , 35 ]. A recent international Cochrane review of trials in dentistry (including 13 U.S. studies) found overall positive (but low-certainty) evidence that brief intervention from dental providers alone increases quit rates, although the level of evidence was more robust (moderate-certainty) when such brief intervention was paired with access to pharmacotherapy [ 36 ]. Research on SBIRT for alcohol and other substance use in dentistry is far more limited.…”
Section: Resultsmentioning
confidence: 99%
“…The multi-component tobacco cessation intervention that we created contains (1) a flip book to guide tobacco cessation based on appropriate BCTs, (2) a short video showing the harmful effects of tobacco to increase awareness, and (3) pharmacotherapy (NRT). Other tobacco cessation interventions delivered in dental settings have also used patient-facing flip books, leaflets and videos as intervention components and some studies used NRT [ 25 ]. Interventions including advice, assistance, and follow-up support, which are effective for the general population, are expected to be applicable for people with diabetes [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dental professionals can use this opportunity to offer tobacco cessation advice [23], although this opportunity is rarely taken [24]. A systematic review by Holliday et al (2021) provided evidence with moderate-certainty that tobacco abstinence rates increase in cigarette smokers if dental professionals offer behavioural support in conjunction with the provision of nicotine replacement therapy (NRT) or e-cigarettes, when compared with no intervention, usual care, or brief, or very brief advice only (RR 2.76, 95% CI 1.58-4.82) [25]. Interventions in the dental setting usually included a multi-component tobacco cessation interventions in conjunction with an oral examination [26].…”
Section: Introductionmentioning
confidence: 99%
“…Vladimirov and colleagues explored the effect of tobacco cessation on a cohort of patients with OLs who had undergone surgical excision, demonstrating that the patients who continued to smoke were significantly more likely to undergo an "unfavourable outcome" (i.e., recurrence of the OL or cancer development) (Vladimirov & Schiodt, 2009). It is feasible for dental offices to perform tobacco cessation (Holliday et al, 2021).…”
Section: Modification Of Known Risk Factorsmentioning
confidence: 99%